Preliminary assessment of two novel mechanical colonoscopic polypectomy simulators: Description, evaluation and validation - Frimberger, Eckart; Klare, Peter; Haller, Bernhard; Elnegouly, Mayada; Bajbouj, Monther; Schmid, Roland M.; von Delius, Stefan; Abdelhafez, Mohamed (Endoscopy International Open, 2020)
Background and study aims Colonoscopic polypectomy is an essential endoscopic skill. The simulators available for training are limited and based on raw porcine colons. Animal intestines are inconvenient and offer limited advantages for polypectomy training. These limitations are avoided by two novel mechanical simulators — the magnetic system based simulator (MSPS) and the simulator for polypectomy with high frequency current (HFPS) — described here. They are equipped to demonstrate self-repair of polyps after making a cut and hybrid polyps. The aim of this study was to describe and establish face, content, and construct validity of the two simulators and to assess their perceived utility as training and assessment tools.Methods Ten novice, seven intermediate, and 10 advanced endoscopists participated in this study. Each one performed two polypectomies in MSPS and then one polypectomy and polyp retrieval in HFPS. The median times were compared among the three groups to preliminarily assess construct validity as a primary outcome. To establish face validity, the novices and intermediates completed a questionnaire about the credibility of each simulator after finishing the tasks. For content validity, the experts completed a questionnaire grading different aspects of the simulators’ realism and their usefulness for training. Results All 27 participants completed the modules. Median times needed to complete the tasks in both simulators differed significantly between the participants with different levels of experience (P < 0.05). Both MSPS and HFPS received favorable scores regarding face and content validity. No technical problems were encountered.Conclusion This study provides preliminary validation for MSPS and HFPS as useful training tools in a preclinical setting as well as during colonoscopy training. Moreover, we demonstrated the construct validity of both simulators, which confirms their use as a skill assessment tool during a colonoscopy training program.